PHASE SEPARATION LIQUID-LIQUID EXTRACTION FOR THE QUANTIFICATION OF 8-ISO-PROSTAGLANDIN F2 ALPHA IN HUMAN PLASMA BY LC-MS/MS - Tomov, Desislav; Bocheva, Georgeta; Divarova, Vidka; Kasabova, Lilia; Svinarov, Dobrin (Journal of Medical Biochemistry, 2020)
Summary Background. Reactive oxygen species (ROS) are produced in the body during normal metabolism by means of enzymes and non-enzymatic chemical reduction of molecular oxygen. In case of prevalence of ROS formation over their elimination, highly reactive free radicals can be accumulated and can cause multiple damages to the biomolecules and cells. Determination of isoprostanes in biological matrices is most often used to register free radical damage and requires selective, sensitive and specific techniques. Methods. This study presents the development and validation of an LC-MS/MS method for the determination of 8-iso-Prostaglandin F2α in human plasma utilising a modified liquid-liquid extraction procedure with phase separation. Results. Modified sample preparation procedure assured higher extraction yield, clear separation of organic layer from plasma water phase and protein precipitates, and better purified product for instrumental analysis. Linearity was validated in the range 0.1 – 5.0 µg/L with R2>0.996; normalised matrix varied between 86.0 and 108.3%, accuracy ranged from 90.4 % to 113.9% and precision both within-runs and between-runs was less than 7%. With a run time of 10 min, a throughput of over 50 samples per working day could be performed. Conclusion. The method meets all the current industrial validation criteria and allows the accurate and precise determination of 8-iso-PGF2α in human plasma at diagnostically significant concentration range.